A compensation algorithm to reduce humidity ratio error due to asynchronous humidity and temperature sensor time constants. (March 2021) - Chen, Wei-Jen; Teng, Tun-Ping
Abstract: Temperature and humidity sensors play a crucial role in the modern environmental control system. However, asynchronous sensor time constants may cause significant measurement errors in humidity ratio and specific enthalpy, which hinders the system operation optimization. In this study, a temperature-relative humidity sensor pair with 7 s of sensor time constant difference is tested. A sealed chamber is built as a closed-system to investigate the induced error magnitude, and a compensation algorithm is proposed to eliminate such error. Experiment results indicate that during a +10 °C/min heating process from 25 °C to 35 °C with initial humidity ratio w = 18.0 g/kg, the humidity ratio supposes to remain constant but instead rise to 28.2 g/kg, representing a maximum 57% error. By using the proposed compensation algorithm, the maximum compensated humidity ratio becomes 19.2 g/kg, corresponding to an 88.9% reduction on the maximum error. The proposed algorithm can be applied to any temperature-humidity sensor pair, showing promising potential in practical applications. Highlights: This study confirms the theoretical humidity ratio error due to asynchronous humidity and temperature sensor time constants. A proposed compensation algorithm can reduce 88.9–97.1% of such errors. The developed algorithm utilizes a swift temperature sensor to boost the laggard RH sensor.